Negative electrode and secondary battery
Patent Information
- Application Number
- JP2023142499
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明によれば、レート特性が良好な二次電池およびそれに用いる負極を提供することができる。
Smart Images

Figure 2025035452000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a secondary battery. [Background technology]
[0002] In an electrode used in a lithium ion battery or the like, an electrode active material layer is formed on a current collector. There are many methods for forming an active material on a current collector when preparing an electrode, but from the viewpoint of whether or not an electrode mixture containing an active material is slurried, the methods can be roughly divided into a wet method and a dry method. In the wet method, an active material, a polymer, a solvent, etc. are mixed to obtain a slurry, and the obtained slurry is applied to a current collector and dried to form an electrode. On the other hand, in the dry method, an electrode is formed without going through a process of applying a solvent and an active material in a slurried state. For example, an electrode is formed by forming a granule containing an active material in advance and pressing it onto a current collector.
[0003] Patent Document 1 discloses a technique of forming granules containing an active material in advance and transferring the granules onto a current collector. Patent Document 1 discloses that in order to suppress poor formation of an active material layer using granulated powder, granulated powder is mixed with flat active material particles, and the particle size and aspect ratio of the flat active material particles are determined. Patent Document 2 discloses an invention in which a magnetic field is applied before pressing to orient elongated graphite in the electrode mixture substantially perpendicular to the current collector foil in order to prevent excessive densification of the electrode mixture layer even when high-pressure pressing is performed and to increase peel strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-100127 A [Patent Document 2] JP 2013-131379 A Summary of the Invention [Problem to be solved by the invention]
[0005] In lithium ion secondary batteries, in order to meet the demand for rapid charging and discharging, it is desirable to use an electrode that has excellent rate characteristics, that is, that can withstand charging and discharging at a large current. Patent Document 1 describes that a homogeneous electrode can be obtained by mixing flat graphite particles and granules to prevent lumping, and the desired thickness and porosity of the active material layer are adjusted by adjusting the gap between the rolling rolls. However, the electrode of Patent Document 1 may not have sufficient rate characteristics. In Patent Document 2, pressure is preferentially applied to elongated graphite oriented approximately perpendicular to the current collector foil to make the electrode mixture less likely to be crushed, but in the method of Patent Document 2, pressure is not easily applied to particles other than those oriented perpendicularly, so that the granules may fall off the active material layer or the current collector foil. Therefore, it is speculated that the electrode of Patent Document 2 also has insufficient rate characteristics.
[0006] As a result of investigations, the inventors have found that in a negative electrode including an active material layer using a granule composed of an active material containing non-spherical particles, a conductive assistant, and a binder, by appropriately adjusting the orientation of the active material, it is possible to obtain a negative electrode with good rate characteristics in which the active material layer is less likely to fall off from the current collector.
[0007] The present invention has been made in view of the above circumstances, and provides a negative electrode having an active material layer that has high adhesion to a current collector, and a secondary battery that uses the negative electrode and has good rate characteristics. [Means for solving the problem]
[0008] That is, according to the present invention, there are provided the following negative electrode and secondary battery. 1. A current collector; an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder; A negative electrode comprising: the active material comprises non-spherical particles; a diffraction intensity ratio I(002) / I(110) of a peak intensity I(002) in a 002 plane to a peak intensity I(110) in a 110 plane, as determined by an X-ray diffraction method of the active material layer, being 100 or more and 300 or less.
[0009] 2. A secondary battery in which the negative electrode described in 1 above and a positive electrode are stacked in multiple layers with a separator between them, optionally rolled up, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode are extended from the outer container. Effect of the Invention
[0010] According to the present invention, it is possible to provide a secondary battery having good rate characteristics and a negative electrode used therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described.
[0012] One embodiment of the present invention is a negative electrode including a current collector and an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder, the active material including non-spherical particles, and a diffraction intensity ratio I(002) / I(110) of a peak intensity I(002) in a 002 plane to a peak intensity I(110) in a 110 plane measured by an X-ray diffraction method of the active material layer being 100 or more and 300 or less.
[0013] In one embodiment, the negative electrode is not particularly limited, but refers to a negative electrode used in a non-aqueous secondary battery material. The negative electrode is composed of a current collector and an active material layer provided on the surface of the current collector, and the active material layer includes an active material, a conductive assistant, and a binder. As the current collector, for example, a metal such as copper, nickel, titanium, or stainless steel can be used. As the current collector, it is preferable to use a flat metal, particularly a metal foil. The current collector will be described in detail later.
[0014] The active material used in one embodiment includes non-spherical particles. Non-spherical refers to any shape other than spherical. Not all particles of the active material are necessarily non-spherical, but all may be non-spherical. The active material particles may include both spherical and non-spherical particles. As the active material, a carbon-based active material can be used. As the carbon-based active material, natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, or any mixture thereof can be selected. Natural graphite includes natural graphite with amorphous carbon coated on the particle surface, and similarly, artificial graphite includes artificial graphite with amorphous carbon coated on the particle surface. These natural graphite and artificial graphite can be primary particles, particles in which primary particles are aggregated to form secondary particles, and mixtures thereof. In addition, a mixture of a carbon-based active material and a silicon-based active material can be used as the negative electrode active material. The negative electrode active material may include metal materials such as aluminum, lithium, silver, bismuth, calcium, cerium, indium, magnesium, tin, zinc, and nickel. The negative electrode active material will be described in detail later.
[0015] The conductive assistant is a material for reducing the resistance of the electrode. Examples of the conductive assistant include carbon black such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon nanotubes, carbon nanofibers, carbon nanobrushes, and other carbon fibers. The conductive assistant will be described in detail later.
[0016] Examples of the binder include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF), conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles, synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile butadiene rubber (NBR), and polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin. Also, examples of the binder that can be used include polyacrylic acid, polymethacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium polymethacrylate, and potassium polymethacrylate; ethyl polyacrylate, ethyl polyacrylate, butyl polyacrylate, methyl polymethacrylate, ethyl polymethacrylate, butyl polymethacrylate, polyacrylamide, and polyacrylonitrile, and any mixtures thereof. Furthermore, as the binder, carboxymethylcellulose (hereinafter referred to as "CMC"), which is a derivative of cellulose, or a metal salt of carboxymethylcellulose (for example, sodium carboxymethylcellulose, potassium carboxymethylcellulose) can be used. The binder will be described in detail later.
[0017] In one embodiment, the active material layer is made of granules. The granules include an active material, a conductive additive, and a binder, and are aggregated together. In one embodiment, the active material layer has the following characteristics: the diffraction intensity ratio I(002) / I(110) between the peak intensity I(002) in the 002 plane and the peak intensity I(110) in the 110 plane, as determined by X-ray diffraction, is 100 or more and 300 or less. Here, the X-ray diffraction method is a method of measuring the spectrum of scattered X-rays by irradiating monochromatic X-rays using CuKα rays as an X-ray source, and a peak specific to the structure of the material irradiated with X-rays is observed. In one embodiment, X-rays are incident on the active material layer, the scattered X-ray spectrum is measured, and attention is paid to the intensity of the (002) plane diffraction peak detected at a diffraction angle 2θ of about 26 to 27 degrees and the (110) plane diffraction peak detected at a diffraction angle 2θ of about 70 to 80 degrees. Attention is paid to the ratio of the peak intensity I(002) in the (002) plane to the peak intensity I(110) in the 110 plane. The diffraction intensity ratio I(002) / I(110) is preferably 100 or more and 300 or less. The diffraction intensity ratio I(002) / I(110) being 100 or more and 300 or less means that the granules constituting the active material layer are not too oriented. It is important to maintain the number of voids (paths) that connect the current collector, which serves as a path for lithium ions, to the surface of the active material layer in order to improve the rate characteristics of a secondary battery using the negative electrode of one embodiment.
[0018] In order to obtain an active material layer having a structure in which the above-mentioned diffraction intensity ratio is observed by the X-ray diffraction method, it is preferable to first form a granule in which the active material, the conductive assistant, and the binder are aggregated, and then to laminate the granule on the current collector to form the active material layer. Here, the granule refers to a granule (granules) in which the above-mentioned active material, the conductive assistant, the binder, and optionally a solvent are used as raw materials and aggregated. The active material layer used in the negative electrode of one embodiment is formed by applying a granule in which the active material, the conductive assistant, and the binder are aggregated to the surface of the current collector by a dry coating method. After forming the active material layer in a state in which the granules are once formed, the active material layer can be pressed so as to obtain a desired density while appropriately adjusting the pressing conditions. It is considered that the granules gradually collapse during pressing of the active material layer, so that the active material particles are not excessively oriented. Compared with an active material layer formed by a wet coating method using a slurry in which an active material, a conductive additive, and a binder are mixed, the active material layer in one embodiment formed using granules has a larger or equal number of pore paths in the thickness direction of the active material layer. The length of the pore paths can be adjusted by changing the pressing conditions such as the number of times of pressing and the pressure while keeping the particle size of the active material and the amount of binder the same (i.e., using the same granules). Here, even in the case of an active material layer formed using granules, if the density is increased without adjusting the pressing conditions, the granules will be crushed back to the original state of active material particles, resulting in the active material being oriented, and the rate characteristics of a secondary battery using a negative electrode including such an active material layer will deteriorate.
[0019] Here, the average particle size of the granules is preferably 15 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more, and is preferably 90 μm or less, more preferably 80 μm or less, and even more preferably 70 μm or less. In one embodiment, the average particle size of the granules means the particle size at an integrated value of 50% (median size: D50) in the particle size distribution (volume basis) measured by a laser diffraction scattering method.
[0020] From the viewpoint of adhesion of the conductive assistant to the active material surface, the average particle size of the active material particles is preferably 1.0 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. And, it is preferably 20.0 μm or less, more preferably 10.0 μm or less, and even more preferably 5.0 μm or less. In one embodiment, the average particle size of the active material particles means the particle size at an integrated value of 50% (median size: D50) in the particle size distribution (volume basis) measured by a laser diffraction scattering method.
[0021] The negative electrode active material includes a carbon-based active material. The carbon-based active material is preferably natural graphite, artificial graphite, hard carbon, soft carbon, or any mixture thereof. Here, graphite is a carbon material having hexagonal plate-like crystals in a hexagonal system, and may be called graphite or the like. The natural graphite and artificial graphite include natural graphite coated with amorphous carbon, and artificial graphite coated with amorphous carbon.
[0022] Here, amorphous carbon refers to a carbon material that is amorphous as a whole and has a random network structure of microcrystals, which may have a structure similar to that of graphite in part. Examples of amorphous carbon include carbon black, coke, activated carbon, carbon fiber, carbon nanotubes, hard carbon, soft carbon, and mesoporous carbon. When using artificial graphite, it is preferable that the interlayer distance d value (d002) is 0.33 nm or more.
[0023] The crystal structure of artificial graphite is generally thinner than that of natural graphite. When artificial graphite is used as a negative electrode active material for a non-aqueous electrolyte secondary battery, particularly a lithium ion secondary battery, it is necessary that the artificial graphite has an interlayer distance that allows lithium ions to be inserted. The interlayer distance that allows lithium ions to be inserted and removed can be estimated by the d value (d002), and if the d value is 0.33 nm or more, lithium ions can be inserted and removed without any problems. In addition, the negative electrode active material may include a silicon-based active material (A) containing SiOx (wherein x is a number that satisfies 0.5≦x≦1.6) and a carbon-based active material.
[0024] The aspect ratio of the negative electrode active material is preferably 1.1 or more and 5 or less. When a granule is prepared that is mainly composed of a negative electrode active material having an aspect ratio in this range, the orientation of the active material layer can be easily adjusted by the pressing conditions, and the electrical characteristics of a secondary battery using a negative electrode having an active material layer with an adjusted orientation are stable. When the aspect ratio of the negative electrode active material is less than 1.1, the active material particles are packed too densely, making it impossible to adjust the orientation of the active material layer, and excellent rate characteristics cannot be obtained in a secondary battery using such a negative electrode. On the other hand, when a granule is formed using an active material with an aspect ratio of more than 5, if the pressing conditions are adjusted to obtain a desired density, the path length formed in the active material layer becomes too long, and the rate characteristics of a secondary battery using such a negative electrode tend to decrease no matter how much the orientation is adjusted. The orientation of the active material layer can be determined by the diffraction intensity ratio I(002) / I(110) of the active material layer. The diffraction intensity ratio I(002) / I(110) of the active material layer is more preferably 50 or more, and even more preferably 100 or more. The diffraction intensity ratio I(002) / I(110) of the active material layer is more preferably 300 or less, and even more preferably 125 or less. As the orientation anisotropy of the active material layer increases, the diffraction intensity I(002) decreases and the diffraction intensity I(110) increases.
[0025] In one embodiment, when the entire granules are taken as 100 parts by mass, the content of the active material is preferably 95.0 parts by mass or more, more preferably 96 parts by mass or more, even more preferably 97 parts by mass or more, and preferably 99.5 parts by mass or less, more preferably 99.0 parts by mass or less, even more preferably 98.5 parts by mass or less. The proportion of the active material involved in the formation of the granules is at least 95% or more, preferably 97% or more, and even more preferably 99% or more.
[0026] The conductive assistant preferably contains at least one selected from the group consisting of carbon black, carbon nanofibers, and carbon nanotubes. The carbon black used as the conductive assistant preferably has an aggregate structure in which carbon nanoparticles are connected in a beaded shape. As the carbon black, acetylene black, ketjen black, etc. can be used. As the conductive assistant, carbon nanotubes formed of a substance composed of carbon atoms such as graphene into a cylindrical shape with a diameter of several nm and a length of several mm can also be used. In particular, single-walled carbon nanotubes formed in a substantially single layer around the cylinder, or multi-walled carbon nanotubes formed in a multiple layer around the cylinder can be used.
[0027] In one embodiment, when the entire granule is taken as 100 parts by mass, the content of the conductive assistant is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.5 parts by mass or less.
[0028] In one embodiment, the granules further contain a binder. It is preferable that the conductive assistant and the binder are present on the surface of the active material particles, and the binder and the conductive assistant are present on the surface and inside of the granules. In this way, when the granules are pressed, the pores between the active material particles are not crushed too much and are not oriented too much, so that a desired density can be obtained.
[0029] The binder may include, for example, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), polytetrafluoroethylene, polyimide, polyamideimide, polyamide, styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinyl alcohol, polyvinyl butyral, or two or more of these, but is not limited to these, and can be changed appropriately depending on the solvent.
[0030] In one embodiment, when the entire granules are taken as 100 parts by mass, the content of the binder is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less.
[0031] A method for manufacturing a negative electrode according to one embodiment preferably includes a step of forming granules by spraying and adding a dispersion liquid in which a conductive assistant is dispersed to the active material particles while mixing and stirring the active material particles, and a step of placing the granules on a current collector and pressing the granules. The method for forming the granules is not particularly limited, and examples of the method include a spray granulation method, an agitation granulation method, a fluidized bed granulation method, a rolling granulation method, an extrusion granulation method, and a compression granulation method. These granulation methods may be selected or combined as desired. An example of the spray granulation method is a spray drying granulation method. In the spray drying granulation method, for example, a dispersion liquid in which a negative electrode active material and a conductive assistant are dispersed is sprayed into a high-temperature gas in a spray dryer to perform granulation. In the agitation granulation method, for example, a dispersion liquid in which a conductive assistant is dispersed is sprayed and added to the negative electrode active material particles while mixing and stirring the negative electrode active material to perform granulation. The average particle size of the granulated particles is preferably 15 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more, and is preferably 90 μm or less, more preferably 80 μm or less, and even more preferably 70 μm or less. The average particle size of the granulated particles means the particle size (median size: D50) at an integrated value of 50% in the particle size distribution (volume basis) measured by a laser diffraction scattering method. By adjusting the number of presses and the press pressure for the active material layer containing the granules thus formed, the adhesion between the current collector and the active material layer is high, and the desired pore paths between the active material particles are maintained to obtain the desired electrode density.
[0032] By attaching a dispersion containing a conductive assistant and a binder that have been highly dispersed in advance to active material particles without containing any other organic solvent, it is possible to prepare an active material with a conductive assistant uniformly formed on the surface. The diameter of the granules formed varies depending on the equipment used to mix and stir these materials, but it is possible to control the diameter by the amount and timing of spraying the dispersion of the conductive assistant and the binder, the mixing and stirring times, and other conditions. In addition, by classifying the formed granules through a sieve, it is possible to obtain granules with any particle size distribution.
[0033] In one embodiment, the material of the current collector is not particularly limited, but when the current collector is a positive electrode current collector, it is preferably aluminum foil. When the current collector is a negative electrode current collector, it is selected from the group consisting of copper, stainless steel, nickel, titanium, or an alloy thereof, and copper is particularly preferred. The shape of the current collector layer is not particularly limited, and may be foil, flat plate, or mesh. For example, the thickness is 0.001 mm or more and 0.5 mm or less.
[0034] When the granules are placed on the surface of the current collector or the surface of the current collector and pressed, the pressing method is not particularly limited as long as the electrode granules containing the electrode active material can be formed on the current collector. In one embodiment, it is preferable to use a roll-type pressure molding method. In the roll-type pressure molding method, a long current collector is arranged so that the current collector passes between a pair of rolls while the current collector is unwound from a roll body wound in a roll shape and wound up. The granules are supplied onto the current collector before passing through the rolls, and are compressed when passing between the rolls to form an electrode sheet. In order to adjust the supply amount of the granules, it is preferable to supply the thickness while smoothing the surface with a squeegee or the like before supplying them between the rolls. It is preferable to previously form a current collector surface layer containing a binder to enhance the binding property with the granules on the current collector. By adjusting the number of times of pressing the electrode sheet, the pressing pressure, the temperature, etc., it is possible to adjust the adhesion between the active material layer and the current collector and the length of the path of the voids between the active material particles.
[0035] A second embodiment of the present invention is a secondary battery in which the above-mentioned negative electrode and positive electrode are stacked in multiple layers with a separator interposed therebetween, optionally rolled up, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode are drawn out from the outer container. The secondary battery of the second embodiment can be produced using the above-mentioned negative electrode in accordance with a known method. In the second embodiment, the positive electrode is not particularly limited, but refers to a positive electrode used in a non-aqueous secondary battery material. For example, the positive electrode is composed of a positive electrode current collector and a positive electrode active material layer provided on the surface of the positive electrode current collector, and the active material layer includes a positive electrode active material, a conductive additive, and a binder. The positive electrode active material layer including the positive electrode active material, the conductive additive, and the binder can be formed on at least one surface of the positive electrode current collector. The positive electrode current collector can be made of stainless steel, aluminum, nickel, titanium, or aluminum whose surface has been treated with carbon, nickel, titanium, or silver.
[0036] Positive electrode active materials include composite oxides of lithium and transition metals such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide; transition metal sulfides such as TiS2, FeS, and MoS2; MnO, V2O5, and V6O 13, one or more selected from the group consisting of transition metal oxides such as TiO2; and olivine-type lithium phosphates. The olivine-type lithium phosphate contains, for example, one or more elements selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, lithium, phosphorus, and oxygen. These compounds may be those in which some elements are partially substituted with other elements to improve their properties. Among them, as the positive electrode active material, Li with an average particle size of 3 to 15 μm a Ni b Mn c Co d M x O2 (where a, b, c, d, x satisfy 0.9 ≦ a ≦ 1.2, 0 < b < 1, 0 < c ≦ 0.5, 0 < d ≦ 0.5, 0 ≦ x ≦ 0.3, b + c + d = 1, and M is at least one selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr), it is preferable to use lithium nickel manganese cobalt oxide represented by As a binder that forms a positive electrode and a material layer together with the positive electrode active material, fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF), conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles, synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), acrylonitrile-butadiene rubber (NBR), or polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin can be mentioned. As the conductive assistant, carbon blacks such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon fibers such as carbon nanofibers, carbon nanotubes, and carbon nanobrushes can be mentioned. In addition, electrode additives generally used for electrode formation, such as thickeners, dispersants, and stabilizers, can be appropriately used in the positive electrode active material layer.
[0037] In the second embodiment, the separator may be, for example, a porous separator. The separator may be in the form of a membrane, a film, a nonwoven fabric, or the like. The porous separator may be a polyolefin-based porous separator such as a polypropylene-based or polyethylene-based porous separator; or a porous separator formed of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, or a polyvinylidene fluoride-hexafluoropropylene copolymer, or the like.
[0038] The separator may contain inorganic particles, such as ceramic particles, or may further contain a layer containing inorganic particles.
[0039] In the secondary battery of the second embodiment, a negative electrode and a positive electrode are laminated with a separator therebetween, and may be wound and housed in an outer container. The secondary battery is formed by drawing out a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode from the outer container. For the outer container, for example, a flexible film having a resin layer on the front and back sides of a metal layer such as aluminum as a base material, or a can made of a metal such as aluminum, iron, or stainless steel can be used. The positive electrode terminal can be made of aluminum or an aluminum alloy, and the negative electrode terminal can be made of copper or a copper alloy or a copper alloy plated with nickel.
[0040] The shape of the secondary battery according to the second embodiment may be, for example, a square, cylindrical, coin or button type housed in an outer container using an aluminum can, an iron can, a stainless steel can, etc. Also preferred is a pouch-type secondary battery housed in an outer container mainly made of an aluminum film.
[0041] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above may also be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0042] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0043] <Production of negative electrodes> (Examples 1 to 4 and Comparative Example 1) Separately from the formation of the conductive layer and the adhesive layer, granulated particles for the negative electrode active material layer were prepared. A negative electrode dispersion liquid was prepared by highly dispersing the negative electrode active material particles, which were artificial graphite with an average particle size of 12 μm and silicon monoxide with an average particle size of 5 μm, single-wall carbon nanotubes (SWCNT) as a conductive assistant, and polyacrylic acid (PAA) and styrene butadiene rubber (SBR) as binders together with a solvent. Next, the negative electrode dispersion liquid prepared by the above procedure was sprayed by rotating the atomizer at a predetermined rotation speed in a spray dryer to obtain granules. The mass ratio of artificial graphite / silicon monoxide / SWCNT / PAA / SBR was 93.45:4.0:0.05:0.5:2.0. Artificial graphite manufactured by Nippon Graphite Industries Co., Ltd., PAA manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and SWCNT manufactured by OCSiAl Corporation can be used.
[0044] Next, a predetermined amount of the obtained granules was supplied onto a current collector traveling from the unwinding side to the winding side of the electrode coater while smoothing the surface with a squeegee. An adhesive auxiliary layer containing carbon black and binders (CMC and SBR) had been formed in advance on the surface of the current collector. After the granules were supplied onto the current collector, the amount of granules supplied to the press roll by the squeegee roll was adjusted before the granules were compressed by the press roll, and then the granules were passed between the press rolls to form an active material layer of the desired density. Negative electrodes with different diffraction intensity ratios I(002) / I(110) were prepared.
[0045] Comparative Example 2 A slurry containing graphite as the negative electrode active material, acetylene black as a conductive additive, and styrene-butadiene copolymer rubber (SBR) as a binder was prepared, and applied to the copper foil as the negative electrode current collector using a die coater, dried, and then pressed with a roll press machine to produce a density of 1.65 g / cm.3 The graphite used was from Nippon Graphite Industries Co., Ltd. <Battery manufacturing> The positive electrode active material is LiNi with an average particle size of 4.5 μm. 0.92 Mn 0.03 Co 0.05 A slurry containing lithium nickel manganese cobalt oxide represented by O2, carbon black as a conductive additive, and polyvinylidene fluoride (PVDF) as a binder was applied to an aluminum foil as a positive electrode current collector, and then pressed to produce a positive electrode with a density of 3.5 g / cm. 3 A positive electrode of 1000 nm was obtained.
[0046] The eight positive electrode layers and the nine negative electrode layers of each of the previously obtained examples or comparative examples were laminated through a polyolefin-based porous separator, and a negative electrode terminal electrically connected to each negative electrode and a positive electrode terminal electrically connected to each positive electrode were provided to obtain a laminate. Next, an electrolyte solution in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate (ethylene carbonate:diethyl carbonate=3:7 (volume ratio)) to a concentration of 1.0 mol / L was placed together with the obtained laminate in a container with a flexible film as a case, and the container was sealed with the positive electrode terminal and the negative electrode terminal pulled out to the outside to obtain a secondary battery.
[0047] <Rate characteristics> The fabricated battery was charged at a constant current of 0.2C up to 4.2V, then switched to a constant voltage after reaching 4.2V and charged down to 0.015C, and discharged at constant currents of 0.2C and 3C down to 2.5V, and the rate characteristics were determined as 3C / 0.2C, which is the ratio of the capacity of the 3C discharge to the 0.2C discharge at 2.5V. Generally, the higher the current value, the more likely the capacity is to decrease, so the closer to 100%, the better the rate characteristics are.
[0048] <Diffraction intensity ratio> The diffraction intensity ratio I(002) / I(110) was calculated as the ratio of the peak intensity I(002) on the 002 plane to the peak intensity I(110) on the 110 plane by X-ray diffraction of the active material layer. The (002) and (110) diffraction peaks of the active material layers of the negative electrodes of the examples and comparative examples were measured using an X-ray diffraction device (SmartLab9kW, Rigaku), and the diffraction intensity ratio I(002) / I(110) was calculated from the peak top intensities. In the X-ray diffraction method, the X-ray source was CuKα radiation / 40KV / 20mA, and the step width was 0.02°.
[0049] [Table 1]
[0050] As shown in Table 1, good rate characteristics were obtained for the secondary batteries (Examples 2, 3, and 4) using a negative electrode having an active material layer with a diffraction intensity ratio of 100 to 300. The rate characteristics of the secondary battery (Example 1) using a negative electrode having an active material layer with a diffraction intensity ratio of 50 are somewhat low because the density of the active material layer after pressing could not be increased sufficiently to achieve a diffraction intensity ratio of 50 in the active material layer using the granules of the present invention, resulting in insufficient contact of the conductive assistant between the active material particles and making it somewhat difficult to follow rapid charging and discharging. On the other hand, in a negative electrode having an active material layer with a diffraction intensity ratio exceeding 400, there are fewer paths perpendicular to the current collector surface and the negative electrode surface, and relatively more paths parallel to the current collector surface and the electrode surface. This is thought to result in a longer path length for the lithium ions, resulting in a deterioration in rate characteristics.
[0051] The electrode for a lithium ion secondary battery and the lithium ion secondary battery of the present invention have been described in detail above. However, the present invention is not limited to the above-mentioned embodiments and examples, and various improvements and modifications may be made without departing from the spirit and scope of the present invention.
Claims
1. A current collector; an active material layer provided on a surface of the current collector, the active material layer including an active material, a conductive additive, and a binder; A negative electrode comprising: the active material comprises non-spherical particles; a diffraction intensity ratio I(002) / I(110) of a peak intensity I(002) in a 002 plane to a peak intensity I(110) in a 110 plane, as determined by an X-ray diffraction method of the active material layer, being 100 or more and 300 or less.
2. The negative electrode according to claim 1 , wherein the active material layer includes granules in which the active material, the conductive additive, and the binder are aggregated.
3. 2. The negative electrode according to claim 1, wherein the aspect ratio of the non-spherical particles is 1.1 or more and 5 or less.
4. A secondary battery comprising a negative electrode according to any one of claims 1 to 3 and a positive electrode stacked together with a separator therebetween, optionally wound, and housed in an outer container, and a positive electrode terminal electrically connected to the positive electrode and a negative electrode terminal electrically connected to the negative electrode being pulled out from the outer container.
Citation Information
Patent Citations
Manufacturing method of battery electrode and battery electrode
JP2013131379A
Method for manufacturing lithium ion secondary battery electrode
JP2016100127A